RE-DESAIN PACKAGING PRODUK KOPI KINIKO DI TABEK PATAH - FADILLA RAHMI, Hendra Afriwan, S.Sn., M.Sn., Elia Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Kiniko Enterprise UKM in Tabek Patah, Batusangkar is a UKM engaged in food processing industry and traditional beverages as well as the tourism industry. This is through the use of culinary wealth and natural beauty of West Sumatra. One of the excellent products of this UKM is Robusta Coffee original West Sumatra. However, there is a weakness in the packaging of products, where packaging does not have a consistency of design and lack of attractiveness. In addition, the packaging of products is also not in accordance with the packaging of good coffee.This final work aims to get the design of packaging design more interesting and have differentiation value to Robusta coffee packaging owned by KINIKO ENTERPRISE. Packaging will be designed with a traditional-modern concept combined with warm-hearted colors. Differentiation will also be seen through the illustrations to be used. The design begins with collecting data through observation, interviews and documentation. Furthermore, the data analysis method is done through SWOT analysis (Strenght, Weakness, Oportunity, Treatment) which is then done by creative designing. In the design of packaging design shown through the layout, illustrations and attractive colors so get the right packaging design.The attractive and characteristic packaging designs will have appeal and are easy to remember by consumers, thereby increasing sales and competitiveness.Keywords: Packaging Design, Coffee, Kiniki Enterprise.